Exploring humour within the early childhood period from children’s and teachers’ perspectives - Betül Yılmaz; Feyza Tantekin Erden (Journal of Childhood, Education & Society, 2022)
The purpose of this study was to examine humour from the perspectives of 60-72-month-old children and their teachers in Turkey. A phenomenological method was used to collect data through semi-structured interviews, which included each child making a drawing about something they thought was ‘funny’. Teachers were also interviewed via semi-structured questions related to children’s humour. Data collected from 22 children and five teachers were analysed using McGhee’s humour development theory and Martin’s descriptions of four humour styles. The humour produced by our sample mainly included items related to incongruity. Teachers described children’s humour development in terms of how the children behaved within their social group, and some believing that children who do not make jokes about their peers, have no humour development. Our findings pointed to a lack of awareness of the benefits of humour to the learning process and early years’ education, particularly with teachers needing to account for age, developmental level and cultural differences.